2002
DOI: 10.1002/cne.10347
|View full text |Cite
|
Sign up to set email alerts
|

N‐methyl‐D‐aspartate receptor blockade inhibits estrogenic support of dendritic growth in a sexually dimorphic rat spinal nucleus

Abstract: The lumbar spinal cord of rats contains the sexually dimorphic, steroid-sensitive spinal nucleus of the bulbocavernosus (SNB). Dendritic development of SNB motoneurons requires the action of both androgens and estrogens. Estrogenic effects are limited to the initial growth of SNB dendrites through 4 weeks of age. During this postnatal period, dendritic growth in other spinal motoneurons is regulated by N-methyl-D-aspartate (NMDA) receptor activation. In this study, we tested whether NMDA receptor activation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(66 citation statements)
references
References 91 publications
7
58
1
Order By: Relevance
“…Previous studies have demonstrated that neither axonal transport of BHRP (Leslie et al, 1991) nor dendritic transport as demonstrated by the rostrocaudal or radial extent of dendritic labeling (Kurz et al, 1991;Goldstein and Sengelaub, 1994;Hebbeler et al, 2002;Fargo and Sengelaub, 2004b) are affected by hormone levels. Thus, in the present study, we believe that the differences we observed across hormone treatment groups reflect true dendritic atrophy in surviving motoneurons in untreated and estradiol-treated animals, which is attenuated by treatment with androgens.…”
Section: Morphometrymentioning
confidence: 89%
See 1 more Smart Citation
“…Previous studies have demonstrated that neither axonal transport of BHRP (Leslie et al, 1991) nor dendritic transport as demonstrated by the rostrocaudal or radial extent of dendritic labeling (Kurz et al, 1991;Goldstein and Sengelaub, 1994;Hebbeler et al, 2002;Fargo and Sengelaub, 2004b) are affected by hormone levels. Thus, in the present study, we believe that the differences we observed across hormone treatment groups reflect true dendritic atrophy in surviving motoneurons in untreated and estradiol-treated animals, which is attenuated by treatment with androgens.…”
Section: Morphometrymentioning
confidence: 89%
“…Average dendritic length per labeled motoneuron was estimated by summing the measured dendritic lengths of the series of sections, multiplying by two to correct for sampling, then dividing by the total number of labeled motoneurons in that series. This method does not attempt to assess the actual total dendritic length of labeled motoneurons (Kurz et al, 1991), but has been shown to be a sensitive and reliable indicator of changes in dendritic morphology in normal development (Goldstein et al, 1990, in response to hormonal manipulation (Kurz et al, 1986(Kurz et al, , 1991Forger and Breedlove, 1987;Goldstein et al, 1990;Sengelaub, 1993, 1994;Burke et al, 1997Burke et al, , 1999Hebbeler et al, 2001Hebbeler et al, , 2002Hebbeler and Sengelaub, 2003), after changes in dendritic interactions and afferent input (Kalb, 1994;Hebbeler et al, 2002;Hebbeler and Sengelaub, 2003), and after the death of nearby motoneurons (Fargo and Sengelaub, 2004a,b).…”
Section: Morphometrymentioning
confidence: 99%
“…Injections of the NMDA receptor antagonist MK-801 into intact males or estradiol-treated castrates attenuates dendritic growth through P28. These results suggest that dendritic development in the SNB involves NMDA receptors, and furthermore that the component of SNB dendritic development sensitive to estrogens requires their activation (Hebbeler et al, 2002). …”
Section: Dendritic Developmentmentioning
confidence: 92%
“…normal development 24,33,34 , after changes in dendritic interactions 33 and afferent input [35][36][37] , and after injury 6,[21][22][23]38 .…”
Section: Dendritic Lengthmentioning
confidence: 99%
“…The portion of each animal's dendritic arbor per labeled motoneuron contained within each location was then determined. This method provides a sensitive measure of dendritic redistribution in response to changes in dendritic interactions 33 and afferent input 35,36 .…”
Section: Dendritic Distributionmentioning
confidence: 99%